Assessing High-Risk Manual Handling Activities for Musculoskeletal Disorders (MSDs) in PT DNL Warehouse Using Rapid Entire Body Assessment (REBA) and Manual Handling Assessment Chart (MAC) Tools - Putri, Meylia Vivi Putri; Nugraha, Widi Nugraha; Safitri, Khoerun Nisa Safitri (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2024)
Musculoskeletal disorders (MSDs) represent a significant occupational health issue, particularly in sectors involving frequent manual handling, which is a major contributor to MSDs risk. The high incidence of MSDs among warehouse workers underscores the critical need for thorough risk analysis in manual handling activities to enhance worker health and safety and reduce associated injuries. This study contributes to this effort by analyzing MSD risks specifically in the warehouse environment of PT DNL, employing two established assessment methods: The Rapid Entire Body Assessment (REBA) and The Manual Handling Assessment Chart (MAC) Tool. By systematically observing manual handling tasks, data were collected and evaluated to determine the level of MSD risk faced by workers in these high-exertion activities. The REBA analysis revealed that workers’ postures, especially during tasks such as unloading from lower stacks and repositioning for distribution, carry a very high risk, with a total score of 11. Similarly, the MAC Tool assessment identified critical risk factors, with lifting operations scoring 17 (indicating four high-risk factors) and carrying operations scoring 15 (indicating two high-risk factors). These findings point to immediate intervention requirements, with recommendations such as using hydraulic lift tables and automatic pallets to reduce bending, alongside instituting guidelines to ensure packages are easy to handle, like incorporating box handles. This research provides a valuable framework for MSD risk reduction strategies in manual handling, contributing to improved occupational safety standards in warehouse operations.